ETHNIC CONSCIOUSNESS AND REINTERPRETATION OF HERITAGE OF THE KAZAKH MUSICAL CULTURE IN 1970-1990-IES - Raimkulova Aktoty (Scientific Journal of Pedagogy and Economics, 2020)
Various disparate phenomena of musical life, discoveries and changes in the paradigm of musicology in the 1970-1990s add up to a single picture of the growth of ethnic self-awareness and reappraisal of the cultural heritage of all historical periods, which prepared the latest stage in the history of musical culture of Kazakhstan. A return to the roots is understood both as a revival of disappearing genres (for example, aitys is a contest of akyns in poetic eloquence), as propaganda of original, traditional art, and as a creative rethinking of cultural heritage. In Kazakhstan, interest in the past was naturally reflected in musicology and in composer creativity. By the 1980s, a school of Kazakh musical folklore was formed. Two trends appeared in composer creativity: the “modernization” of folklore through the complication of the musical language of its transcriptions on the one hand and the development of folklore elements within the framework of new composer techniques of the 20th century on the other. A key factor in the process of reinterpreting the heritage of Kazakh musical culture in the 1970-1990s is ethnic identity. It is expressed in composers’ creativity, in ethnomusicology, and in understanding the role of Kazakh musical culture in the world. All these processes have prepared a paradigm shift in the culture of the post-Soviet period.